تحليل مغلف البيانات: دراسة مقاربات البيانات النوعية وغير الدقيقة - عشي, عادل; بومجان, عادل (Recherches économiques et managériales; Vol. 12 No 02 (2018): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(Décembre), 2020)
يعتبر أسلوب تحليل مغلف البيانات من الأساليب المستخدمة بكثرة في قياس كفاءة الوحدات الإنتاجية. وتفترض نماذجه التقليدية أن تكون المدخلات والمخرجات كمية ودقيقة. وفي الواقع قد يتعذر تحقق هذا الفرض وبالتالي تعذر تطبيق النموذج التقليدي مع هذا النوع من البيانات. تأتي هذه الورقة  من أجل استعراض أهم المقاربات المعروفة في معالجة مثل هذه الوضعيات. الكلمات الدالة : تحليل مغلف البيانات؛ كفاءة؛ بيانات غير دقيقة؛ بيانات نوعية؛ بيانات ترتيبية.   Abstract :    Data envelopment analysis (DEA) is well-known as a method for measuring efficiency and performance of decision making units. Conventional DEA models assume deterministic, precise and quantitative data for input and output observations. However, in many cases these assumptions are violated and some input and output observations are qualitative and imprecise. The current paper presents some approaches for dealing with qualitative and imprecise data when measuring efficiency by DEA.    Keywords: Data envelopment analysis; Efficiency ; Imprecise data; qualitative data; ordinal data.